Avaliação experimental da fragmentação do hábitat em comunidades de macroinvertebrados associados a macroalgas - Daunt, Ana Beatriz Pierri (2013)
Habitat fragmentation is a major cause of biodiversity loss, so understanding the effects of habitat fragmentation on the structure and dynamics of natural communities is very important to biodiversity conservation. This study evaluated whether habitat fragmentation affects the structure of macroinvertebrate communities associated with macroalgae in the sublittoral of a protected shore in the northern coast of São Paulo State. First, we carried out an experiment to evaluate the colonization of the aquatic fauna to substrates with different structural characteristics after two and four weeks for colonization (Chapter II). Our results showed that the tubular plastic net exposed to four weeks of colonization would be efficient to the execution of the fragmentation experiment (Chapter III). Then, we built artificial landscapes that formed large patches, which were later fragmented to analyse the development of communities relative to position within the patches (edge vs. interior) and resulting patch size . Higher taxon richness and gastropod abundance were recorded in the patch edge, but no significant differences were found among patch sizes. We found a significant effect of fragmentation, with lower abundances of Gammaridea (the dominant taxon), Ophyuroidea and Pycnogonida after the experimental fragmentation. Edge environments may shelter higher richness and abundance of organisms due to higher inputs of food and organism settlement. The lack of experimental studies in this systems makes it difficult to determine the appropriate spatial scale to study and to interpret patch size differences. Our results support the importance to preserve seaweed beds for the conservation of macroinvertebrate diversity, independently of patch sizes. Thus, these results can help to understand the effects of habitat fragmentation in marine systems, supporting management actions for biodiversity conservation.